The effects of pregnancy on the progression of maternal glomerular disease - Luiz Paulo José Marques; Lívia Menezes Salla; Lilimar da Silveira Rioja; Regina Rocco; Eugênio Pacelle Queiroz Madeira; Lygia Maria Soares Fernandes Vieira (Brazilian Journal of Nephrology)
Abstract Introduction: Although most women with underlying glomerular diseases (GD) are of childbearing age, there is limited information on how pregnancy affects these conditions and maternal outcomes. Methods: We carried out a single-center retrospective cohort study involving 44 planned pregnancies in 38 patients with biopsy-proven GD. Patients were divided into three groups based on their pre-conception CKD-KDIGO classification: I) Stage 1–2: 27 pregnancies, II) Stage 3a–3b: 11 pregnancies, and III) Stage 4–5: 6 pregnancies. Clinical data included age, chronic hypertension (CH), serum creatinine, preeclampsia (PE), and proteinuria. We considered CH, CKD stage before pregnancy, and PE and nephrotic proteinuria (NPu) during pregnancy as risk factors for maternal GD progression. Results: We found that 8 women progressed to ESRD and began hemodialysis during pregnancy: 2 (7.8%) in Group I, 1 (9.0%) in Group II, and 5 (83.3%) in Group III. In the remaining 36 pregnancies, we observed a significant GFR loss (p < 0.0001) one year after pregnancy, and GFR loss was greater in group II than in I (p < 0.013). Low GFR rates before pregnancy and PE during pregnancy (p = 0.001) directly impacted GFR loss. We also observed a high incidence (63.6%) of adverse fetal outcomes. Conclusion: Although pregnancy is possible for women with GD, the impact of pregnancy in maternal GD continues after delivery. Having GD increases the risks of adverse pregnancy outcomes. The progression of GD is directly linked to the CKD stage before pregnancy and PE during pregnancy, and women in CKD stages 4–5 have a high risk of progressing to ESRD during gestation.